ANALISIS PENGARUH VARIABEL MAKROEKONOMI REGIONAL TERHADAP TINGKAT KEMISKINAN PERKOTAAN - Nursetyo Yekti Hapsoro, Dody; Agung Gunanto, Edy Yusuf (Diponegoro Journal of Economics, 2013)
Poverty is a multidimensional problem, it’s involves various aspects of life, from the economic to the social. The spread of poor people in Indonesia focused on urban and rural areas. Urban poverty becomes an increasingly relevant issue to be addressed, related to the dynamics of urban development and population growth that accompanies. Trend of population urbanization in Indonesia was followed by further poverty urbanization, it’s impact on the incidence  of various aspects of the urban poverty problems and urban poverty have  rigidity to decline, if compared to rural areas.Regional economic stability have influential on poverty, some macroeconomic variables be indicator. Efforts to address poverty should refer to the development of these variables. The purpose of this study was to analyze a regional macroeconomic variable, in this case GRDP, unemployment, and inflation in urban areas during the period 2007-2010.This study, uses secondary data in panel data form, consisting of time series data over the  period 2007-2010 and a cross section 44 cities in Indonesia. The approach to estimate the panel  data is Fixed Effect Model (FEM), by including a dummy variable in the equation, also known as the Least Square Dummy Variable (lSDV).  Dummy variables  regions  used  in  this  research  model  because of  each difference in the characteristics and resources of each region.The results showed that GRDP variables have significant negative effect on poverty.   Meanwhile,  unemployment  and  inflation  variables  have  positive  and significant impact on poverty. Thus, GRDP, unemployment, and inflation is worth a consideration in formulating policies to address the problem of urban poverty.